Tradition meets modernity: understanding consumer psychology for TCM functional foods in Northern China using integrated structural equation and agent-based modeling - Zhao, Zujian; Chen, Lin (Frontiers in Psychology, 2025)
The expanding market for Traditional Chinese Medicine (TCM) functional foods presents a dynamic tension between deep-seated cultural heritage and contemporary consumer cognition. This study develops and validates an integrated theoretical framework using survey data from Northern China consumers. The research introduces and empirically validates a new construct, “Medicine-Food Separation Cognition” (MFSC), representing a modern, categorical mindset that emerges as a key cognitive barrier to market acceptance, particularly pronounced in urban environments. The findings establish Cultural Identity as a foundational driver of consumer affinity for these products, while demonstrating how contextual factors systematically influence cognitive schemas within the digital health ecosystem. By translating psychological insights into agent-based modeling, the study explores potential market-level consequences of individual-level factors. The integrated methodology offers both a theoretical tool (MFSC) and a replicable analytical framework for understanding culturally significant wellness markets. These findings provide actionable insights for developing segmented strategies in culturally embedded health product markets and informing regionally-tailored policies for sustainable consumption in Northern China and analogous settings.